Comparison of Tigecycline or Cefoperazone/Sulbactam therapy for bloodstream infection due to Carbapenem-resistant Acinetobacter baumannii - Tianshui Niu; Qixia Luo; Yaqing Li; Yanzi Zhou; Wei Yu; Yonghong Xiao (2019)
We retrospectively analyzed the effect of tigecycline and cefoperazone/sulbactam therapies on the prognosis of patients with carbapenem-resistant Acinetobacter baumannii bloodstream infection (CRAB-BSI). CRAB-BSI patients receiving tigecycline therapy or cefoperazone/sulbactam therapy between January 2012 and December 2017 was enrolled, and strict exclusion criteria were followed. The 28-day mortality of patients was analyzed. The impact of cefoperazone/sulbactam therapy on prognosis was evaluated using Cox multivariate regression analysis. The 28-day mortality of patients receiving cefoperazone/sulbactam monotherapy and cefoperazone/sulbactam-based combination therapy was also compared. Three hundred forty eight patients with CRAB-BSI were enrolled in the study. Two hundred ten patients were included after applying the exclusion criteria. Of these, 135 patients received tigecycline therapy and 75 patients received cefoperazone/sulbactam therapy. The 28-day mortality of patients in the latter group was, significantly lower than that of the tigecycline group [29.3% vs. 51.9%; P = 0.001]. Cox multivariate regression analysis revealed that cefoperazone/sulbactam therapy exerted a protective effect on the prognosis of patients [hazard ratio 0.566, 95% confidence interval (0.342–0.940); P = 0.028]. Kaplan-Meier survival curve analysis indicated that the 28-day mortality of patients receiving cefoperazone/sulbactam therapy was lower than that of patients receiving cefoperazone/sulbactam monotherapy, but the difference was not significant (22.2% vs. 40%; P = 0.074). However, the mortality of patients receiving cefoperazone/sulbactam with imipenem/cilastatin was significantly lower than that of patients receiving cefoperazone/sulbactam monotherapy (P = 0.048). Patients treated with cefoperazone/sulbactam therapy had a better clinical outcome. The mortality of patients receiving cefoperazone/sulbactam with imipenem/cilastatin seems to be the lowest.